Transcription factors MhyFIL1 and MhyFIL3 (Monotropa hypopitys) determine the asymmetric development of above-ground lateral organs in plants - A. V. Shchennikova (Vavilovskij Žurnal Genetiki i Selekcii, 2019)
It is believed that the complete mycoheterotroph pinesap Monotropa hypopitys adaptively evolved from a photosynthetic mycorrhizal ancestor, which had lost its photosynthetic apparatus and vegetative organs (stem and leaves). The aerial part of the plant is a reproductive axis with sterile bracts and inflorescence with a flower type canonical for higher plants. The origin of leaves and leaf-like lateral organs is associated, among other factors, with the evolution of the YABBY genes, which are divided into“vegetative” and evolutionarily recent“reproductive” genes, with regard to their expression profiles. The study of the vegetative YABBY genes in pinesap will determine whether their functions (identification of cell identity on the abaxial surface of the lateral organs) are preserved in the leafless plant. In this study, the structural and phylogenetic analysis of the pinesap vegetative genes MhyFIL1 and MhyFIL3 is performed, the main conserved domains and motifs of the encoded proteins are characterized, and it is confirmed that the genes belong to the vegetative clade YABBY3/FIL. The effect of heterologous ectopic expression of the MhyFIL1 and MhyFIL3 genes on the phenotype of transgenic tobacco Nicotiana tabacum is evaluated. The leaves formed by both types of plants, 35S::MhyFIL1 and 35S::MhyFIL3, were narrower than in control plants and were twisted due to the changed identity of adaxial surface cells. Also, changes in the architecture of the aerial part and the root system of transgenic plants, including aberrant phyllotaxis and arrest of the shoot and root apical meristem development, were noted. Some of the 35S::MhyFIL1 and 35S::MhyFIL3 plants died as early as the stage of the formation of the first leaves, others did not bloom, and still others had a greatly prolonged vegetation period and formed fewer flowers than normal ones. The flowers had no visible differences from the control except for fragile pedicles. Thus, the absence of structural changes from the M. hypopitys flower in comparison to autotrophic species and the effect of MhyFIL1/3 heterologous expression on the development of tobacco plants indicate the preservation of the functions of the vegetative YABBY genes by the MhyFIL1/3 genes in pinesap. Moreover, the activity of YABBY transcription factors of the FIL clade in M. hypopitys is not directly related to the loss of the ability of pinesap to form leaves during the evolutionary transition from autotrophic nutrition to heterotrophy.